Bringing light to remnants of riparian areas in rice field channels: a combined application of linear transects and the mapping method - Godinho, Carlos (2012)
The importance of rice fields for bird conservation has been subject of several studies, mainly focused in core areas as habitat for waterbirds. However, significant parts of the rice field structure, like the irrigation channels that control the water level, are often neglected. These corridor-like areas are frequently characterized by the presence of riparian vegetation like willows and ashes or wetland vegetation like reedmace or common reedbeds. In order to assess the importance of these landscape features, two rice fields in the western part of Portugal were surveyed during the 2009 breeding season. The main goal was to assess the breeding bird community of these areas. We used a combination of linear transects and mapping method, recording only the singing males.